Pengaruh Strategi Harga dan Produk Furniture Terhadap Perilaku Pembelian Pada Konsumen” (Studi Analisis Metode Verifikatif terhadap Pembeli Furniture Olympic pada Cabang Outlet Carefour MT Haryono - Iswahyu Prana wukir; Hiswanti .; Maria Jashinta Elisabet Hamboer (Jurnal Ilmu Komunikasi PROGRESSIO, 2021)
In quantitative research, verification is a common method used to check whether a method is correct by verifying or without corrections from what has been carried out elsewhere, by taking similar problems in life. The quantitative approach leads to a scientific approach to managerial and economic decision making. This approach consists of problem formulation, finding solutions, testing solutions, analyzing results and implementation of the results in achieving such as measure (calculation).This study aims to verify the role model of the business communication corridor. Analysis will address this question:how much influence a dimension of a strategy consisting of two independent variables, product and price of the Olympic brand furniture has on the dimensions of purchasing behavior as the dependent variable at the outlet at Carrefour MT Haryono, Jl Raya MT Haryono, South Jakarta.This research will apply business communication strategy theory (pricing strategy, product strategy, consumer behavior, purchasing decision and social category in order to represent discipline of social science).For methodology, this research uses a verification study analysis with a positivistic paradigm. Data are referred to population of 450; 82 samples, while in the implementation and research, only 30 respondents were used as samples.This study has resulted an important conclusion about the dimension of price strategy conducted by Olympic brand in that specific outlet. The furniture prices here are actually not cheap and rather close to the expensive in category (it is measured 2,25 at mean scale dimension). It shows the opinion of buyers who think the prices of furniture has a tendency to be expensive.In the dimension of product strategy, it is clear that the products and strategies of Olympic furnitures are particularly targetted the household of urban middle class Indonesian. It can be verified from looking at the quality standard of products which are either not too good or too bad, at least from the eyes of the buyers.The research also finds that the decision to buy an Olympic product is determined by a number of specific indicators, namely: the quality, the price, kind of products and place where products are sold. It has been validated through this research that Olympic furniture products are mostly bought by ordinary buyers. They buy the products spontaneously at the Olympic outlet at Carefour. They are not those regular or typical inexperienced buyers.